Strengthening Curriculum Structure of the Information Systems Programme - Fatihah, Ramli; Mohamad Nazri, Khairuddin Yap; Suhaila, Saee; Rosita, Mohamed Othman; Jennifer Fiona, Wilfred Busu; Alvin Yeo, Wee (Semarak Ilmu Publishing, 2024)
The emergence of the Fourth Industrial Revolution (4IR) in Malaysia was led by a modern lifestyle and new employment market demand. 4IR indirectly has impacts on higher education, particularly in Malaysian higher education. Therefore, the Ministry of Higher Education of Malaysia is forging ahead by revamping the Malaysian education system to prepare future-ready graduates that fit 4IR. In line with the mentioned efforts by other public universities in Malaysia, Universiti Malaysia Sarawak (UNIMAS) also responds to the need for this education transformation. This paper presents a discussion on the experience and processes during the development of the new curriculum structure specifically for the Information Systems Undergraduate Programme at UNIMAS. This paper aims to restructure the existing curriculum into a new curriculum that is in line with MQA requirements.